Biodegradation of reactive orange 16 (RO-16) dye in packed bed bioreactor using seeds of Ashoka and Casuarina as packing medium - Bharti V.; Shahi A.; Geed S.R.; Kureel M.K.; Rai B.N.; Kumar S.; Giri B.S.; Singh R.S. (My University, 2025)
The main objective of this work was to evaluate the performance of Ashoka and Casuarina (abundantly available in India as agrowaste) seeds as packing material with immobilized mixed culture of microorganisms for biodegradation of reactive orange dye (RO-16) in the continuous packed bed bioreactor. The percent removal of RO-16 was increased with time in both cases and attained constant value on the 10th d of operation with maximum removal 63.5±5% and 69.27±5%, respectively for Ashoka and Casuarina seeds, at inlet flow rate of 1.0 LPH and initial concentration of 500 ppm. The second order of kinetics applied and it fitted well for both packing materials. The results demonstrate that the selected seeds have potential as to be used as packing material for biodegradation application in bioreactors.